PUBLIC RELATIONS COMMUNICATION STRATEGY OF MEDAN TUNTUNGAN SUBDISTRICT IN BUILDING PUBLIC TRUST THROUGH INSTAGRAM - Annisa Gika Kaban; Muhammad Jailani (Program Pascasarjana UIN Sumatera Utara, 2026)
Public trust in government institutions constitutes a fundamental foundation for establishing legitimate and accountable governance. This study aims to analyze the communication strategies employed by the Public Relations Office of Medan Tuntungan Subdistrict in building public trust through the management of its Instagram account. The study employed a descriptive qualitative approach using a case study method. Data were collected through interviews, observation, and documentation. The data were analyzed using the four-stage public relations management model developed by Cutlip, Center, and Broom, comprising defining the problem, planning and programming, taking action and communicating, and evaluating the program, and were presented in a narrative form. The findings reveal that the public relations unit implemented a multichannel communication strategy integrating formal news-style Instagram content and persuasive flyers, information dissemination through neighborhood heads and civil servants acting as opinion leaders, and active response mechanisms for addressing public inquiries and misinformation. The effectiveness of this strategy was reflected in tangible changes in public behavior, including a substantial increase in residents visiting the subdistrict office following the publication of public service information. These findings demonstrate that the strategic and consistent management of Instagram plays a significant role in strengthening public trust in subdistrict government institutions.